Optical coherence tomography : atlas and text - Boyd L., Samuel; Rosario Brancato; Straatsma, Bradley (Panamá : Jaypee - Highlights Medical Publishers, 2009)
Optical Coherence Tomography - Atlas and Text presents multiple uses and interpretation of OCT and its applications in ophthalmology related to the posterior segment and the retina. The use of OCT in the diagnosis and treatment of glaucoma, age-related macular degeneration, its integration into fluorescein angiography, as well as its use in the diagnosis and management of ocular tumors is described.
Table of Contents Chapter 1: Introduction to OCT1 Chapter 2: OCT Scan Aplications Protocols and procedures Chapter 3: Application of Optical Coherence Tomography in Ophthalmology Chapter 4: Optical Coherence tomography for exploring the anterior segment of the eye Chapter 5: Architecture of clear corneal incisions Demonstrated by OCT and other more
Incluye índice
Keywords: OPTICAL COHERENCE TOMOGRAPHY; OPTOMETRY; ENFERMEDADES DE LA RETINA